(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This Project presents an automotive localization system using GPS and GSM-SMS services and alerts over IOT for woman security. The system permits localization of the woman and transmitting the position to the rescue team as a short message (SMS) and over Internet. The system can be interconnected with the car alarm system and alert the surrounding people to help woman. This security tracking system is composed of a GPS receiver, Microcontroller, and a GSM Modem and IOT module. When woman need help that time, she will press security alert switch then GPS Receiver gets the location information from satellites in the form of latitude and longitude with alert through IOT. The Microcontroller processes this information, and this processed information is sent to the certain person using GSM modem. The presented application is a low-cost solution for woman in risk. The proposed solution can be used in other types of application like child security, woman security, where the information needed is requested rarely and at irregular period of time (when requested).